PLEONASM AND TAUTOLOGY IN RUSSIAN AND UZBEK: A COMPARATIVE ANALYSIS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article examines the phenomena of pleonasm and tautology in Russian and Uzbek. The structural and semantic features, as well as the functions of these linguistic units in various speech styles are analyzed. Special attention is paid to the cultural and linguistic reasons for the stability and frequency of such constructions.